Nickel-Catalyzed Migratory Arylboration of Nonactivated Alkenes - Wang, Wang; Ding, Chao; Yin, Guoyin (Synlett, 2019)
An unprecedented nickel-catalyzed 1,n-arylboration (n >2) of terminal nonactivated alkenes has been developed. This reaction is the first example of a regioselective arylboration of terminal nonactivated alkenes and features high selectivity, wide functional-group tolerance, and operational simplicity. Remarkably, preliminary mechanistic studies indicated that an equilibrium of various nickel intermediates exists in this transformation, but bond formation is favored at the benzylic position.
Keywords: nickel catalysis; metal migration; arylboration; alkenes; diarylalkanes